1989
DOI: 10.1128/jb.171.3.1245-1253.1989
|View full text |Cite
|
Sign up to set email alerts
|

A single point mutation results in a constitutively activated and feedback-resistant chorismate mutase of Saccharomyces cerevisiae

Abstract: The Saccharomyces cerevisiae ARO7 gene product chorismate mutase, a single-branch-point enzyme in the aromatic amino acid biosynthetic pathway, is activated by tryptophan and subject to feedback inhibition by tyrosine. The ARO7 gene was cloned on a 2.05-kilobase EcoRI fragment. Northern (RNA) analysis revealed a 0.95-kilobase poly(A)+ RNA, and DNA sequencing determined a 771-base-pair open reading frame capable of encoding a protein of 256 amino acids. In addition, three mutant alleles of ARO7 were cloned and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 41 publications
(25 reference statements)
1
49
0
Order By: Relevance
“…EcCM exists as a fusion protein in E. coli and is subject to allosteric inhibition only by pathwayspecific inhibitors (Prakash et al, 2005). The ScCM of S. cerevisiae and AnCM of Aspergillus nidulans are inhibited by Tyr and Phe and are stimulated by Trp (Krappmann et al, 1999;Schmidheini et al, 1989). Similar to MtbCM (Kim et al, 2006), CM0819 in C. glutamicum is not subject to any regulation by aromatic amino acids.…”
Section: Discussionmentioning
confidence: 95%
“…EcCM exists as a fusion protein in E. coli and is subject to allosteric inhibition only by pathwayspecific inhibitors (Prakash et al, 2005). The ScCM of S. cerevisiae and AnCM of Aspergillus nidulans are inhibited by Tyr and Phe and are stimulated by Trp (Krappmann et al, 1999;Schmidheini et al, 1989). Similar to MtbCM (Kim et al, 2006), CM0819 in C. glutamicum is not subject to any regulation by aromatic amino acids.…”
Section: Discussionmentioning
confidence: 95%
“…A constitutively activated yeast CM is known in which the last residue of this particular loop (Thr-226) is substituted by an isoleucine residue. This residue locks the enzyme structure in the allosteric R state, which completely prevents inhibition or further activation (6). The end of this loop, however, is not as strongly conserved among these homologous CMs.…”
mentioning
confidence: 99%
“…It is of interest to note that mutagenesis studies demonstrated that threonine residue 278 was essential for prephenate dehydratase activity (Baldwin & Davidson, 1981). While it appears that the prephenate dehydratases may share a common ancestor, a monophyletic origin of chorismate mutase enzymes is not obvious since the CM-Fs of B. subtilis (Gray et al, 1990) and Saccharomyces cerevisiae (Schmidheini et al, 1989) showed marginal to no similarity to the P. stutzeri P-protein, the E. coli P-protein, the E. coli Tprotein, or to each other. The sequence of the gene encoding the bifunctional DAHP synthase : chorismate mutase from B. subtilis 168 (Hoch & Nester, 1973;Nasser & Nester, 1967) may provide clues about the evolution of chorismate mutase.…”
Section: Evolutionary Relationships Between Enzymes Oj' Phenylalaninementioning
confidence: 99%